Religious outsiders and the making of Americans - Moore, R. Laurence (Robert Laurence), 1940- (New York : Oxford : Oxford University Press, 1986)
In light of the curious compulsion to stress Protestant dominance in America's past, this book takes an unorthodox look at religious history in America. Rather than focusing on the usual mainstream Protestant churches--Episcopal, Congregationalist, Methodist, Baptist, and Lutheran--Moore instead turns his attention to the equally important "outsiders" in the American religious experience and tests the realities of American religious pluralism against their history in America. Through separate but interrelated chapters on seven influential groups of "outsiders"--The Mormons, Catholics, Jews, Christian Scientists, Millennialists, 20th-century Protestant Fundamentalists, and the African-American churches--Moore shows that what was going on in mainstream churches may not have been the "normal" religious experience at all, and that many of these "outside" groups embodied values that were, in fact, quintessentially American.
How to become a people: the Mormon scenario -- Managing Catholic success in a Protestant empire -- American Jews as an ordinary minority -- Christian Science and American popular religion -- Premillennial Christian views of God's justice and American injustice -- The Protestant majority as a lost generation: a look at fundamentalism -- Black culture and Black churches: the quest for an autonomous identity -- Civil and uncivil religions: describing religious pluralism.
Includes index.
Includes bibliographical references (pages 211-235) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Religious pluralism; United States -- Religion; Religious pluralism -- United States; Pluralisme religieux -- États-Unis.; États-Unis -- Religion; RELIGION -- Comparative Religion; Religion; Religious pluralism; United States; Kerkgenootschappen; Godsdiensten; Verenigde Staten; United States -- Religions, to 1978